(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2022)
Balitnak Superior Kampung Chicken (KUB) was a native chicken that has the ability to survive disease. The purpose of this study was to determine whether the substitution of Tomato Fermented Extract (ETF) could affect the productivity of KUB chickens before laying eggs. The materials used were 60 KUB chickens before laying eggs at the age of 12 weeks. EFT and commercial feed. Treatment of drinking water given to chickens is 0, 15, 30, and 45 (%). The design used was a completely randomized design (CRD) which consisted of 4 treatments and 5 replications. Parameters observed were feed consumption, drinking water consumption, average daily growth of chickens, efficiency and conversion, feed. Data were analyzed for variance (ANOVA) followed by UJBD. The results showed that feed consumption was 77.1-135.7 g and showed no significant effect. BK consumption of 66.5 g and PK consumption of 13.4 g. Drinking water consumption of 0.23-0.24 liters has no significant effect. PBBH of 9.05-9.79 g has no significant effect. The feed conversion value of 8.02-8.60 has no significant effect. Feed efficiency of 11.73-12.90% has no significant effect. The conclusion showed that all research parameters, namely feed consumption, drinking water consumption, ADG, feed efficiency and feed conversion, were not significantly different.